2022
DOI: 10.1186/s40854-022-00381-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of investor sentiment on stock volatility: new evidences from multi-source data in China’s green stock markets

Abstract: The effect of investor sentiment on stock volatility is a highly attractive research question in both the academic field and the real financial industry. With the proposal of China's "dual carbon" target, green stocks have gradually become an essential branch of Chinese stock markets. Focusing on 106 stocks from the new energy, environmental protection, and carbon–neutral sectors, we construct two investor sentiment proxies using Internet text and stock trading data, respectively. The Internet sentiment is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 80 publications
(88 reference statements)
0
4
0
1
Order By: Relevance
“…Various external and internal factors can cause price volatility in commodity markets. Huang et al (2011) and Nurlita & Naomi (2019) found that political events or corporate performance can trigger price volatility, while Gao et al (2022) showed market sentiment as another factor influencing price volatility.…”
Section: ______395mentioning
confidence: 99%
“…Various external and internal factors can cause price volatility in commodity markets. Huang et al (2011) and Nurlita & Naomi (2019) found that political events or corporate performance can trigger price volatility, while Gao et al (2022) showed market sentiment as another factor influencing price volatility.…”
Section: ______395mentioning
confidence: 99%
“…(Aggarwal, 2022;Brown & Cliff, 2004;Lee et al, 2002;Verma & Verma, 2008) . (Baker & Stein, 2004;Baker & Wurgler, 2007;Luo, 2012;Naik & Padhi, 2016;Ryu et al, 2017;Seok et al, 2019) (Alnafea & Chebbi, 2022;Baker & Stein, 2004;Baker & Wurgler, 2007;Fu et al, 2021;Luo, 2012;Naik & Padhi, 2016;Ryu et al, 2017;Seok et al, 2019) (Alnafea & Chebbi, 2022;Fu et al, 2021;Gao et al, 2022;Luo et al, 2021;Naik & Padhi, 2016 (Baker & Wurgler, 2007;Lee et al, 1991;Qiu & Welch, 2004) . Chebbi, 2022;Cui & Zhang, 2020;Fan et al, 2021;Fu et al, 2021;Wu et al, 2021;Yin & Tian, 2017) .…”
Section: ‫عر‬ ‫ع‬ ‫ع‬unclassified
“…That is, the cumulative monthly rate of return Sent which considers a cash bonus with a 6-month lag period, is used to measure investor sentiment. At the same time, the cumulative monthly rate of return Sent 0, which does not consider a cash bonus with a 6-month lag period, is used to test the robustness (Gao et al, 2022). Government supervision (GS): It is common practice at home and abroad that the government funds R&D funds, and social forces are involved.…”
Section: Intermediate Variable-investor Sentiment and Government Supe...mentioning
confidence: 99%